THE LEGAL PROBLEMS OF LAND LAW TOWARD INVESTMENT ERA IN INDONESIA - Supriadi, Supriadi; Weri, Asmadi; Sari, Dewi Kemala (Tadulako University, 2018)
The development of the Indonesian nation needs assistance from abroad, through the mechanism of investment, and in the context of investment in Indonesia providing facilities in the field of import duties, and land use permits. The ease of granting permits to use the land is often an obstacle, because there is a clash between the community and large companies, the government and other agencies. To avoid such conflicts, the road taken is to build awareness of all stakeholders, especially government officials and security forces. the people who own / control their land are only intended to connect their lives. Meanwhile, government officials and security forces and law enforcement officials realized that